Predictive factors for local recurrence and distant metastases following primary surgical treatment of phyllodes tumour of the breast - K., Ashwin Hebbar; V., Sushil Kumar B.; Kallapa, Shashidhar; Arif, Mohamad (International Surgery Journal, 2016)
Background:Phyllodes tumours are rare breast tumours that, like fibro adenomas, contain 2 types of breast tissue: stromal (connective) tissue and glandular (lobule and duct) tissue. They are most common in women in their 30s and 40s, but they may also be found in women of any age. They constitute 1% of mammary tumours and 2-3% of fibro epithelial tumours of the breast. The objective of this study was to characterize the risk and predict factors for local and distant recurrence in patients primarily treated with surgery. And whether a subgroup could be identified in whom adjuvant treatment would be needed. Methods: Data from 57 patients treated for phyllodes tumours between January 2008 to December 2012 (5 years) were reviewed retrospectively. Data recorded included age, menopausal status, diagnostic methods, treatment given, histopathology, recurrence and follow up. Preoperative diagnosis was done with fine needle aspiration cytology (FNAC). Work-up with - chest x-ray (CXR) and ultrasound (USG) abdomen. Patient characteristics, pathologic variables and surgical procedures were investigated as predictors of local recurrence and distant metastasis. Results:Age of patients ranged from 30-60 years with a mean of 46 years. 24 patients were pre and 33 were post-menopausal. All patients presented with a self-detected breast lump. Right breast was involved in 33 patients and left in 24 patients. Central quadrant was most commonly involved (24 patients). 6 of our patients had clinically enlarged auxiliary nodes (FNAC - reactive). We performed simple mastectomy and wide local excision of the tumour. Histopathologically, 6 were benign, 24 were borderline and malignant were 27. Depending on histopathological report adjuvant treatment were given. Conclusions:Preoperative diagnosis of phyllodes tumour of the breast is very crucial. The type of surgery, histological type, stromal overgrowth, cellular atypia and mitotic count were important factors in predicting local recurrence. The surgical margin, histological type, stromal overgrowth, cellular atypia and mitotic count were important factors in predicting distant metastasis. To prevent recurrence, wide local excision with at least 1 cm margin is preferred for benign and borderline types. Malignant types should be treated with simple mastectomy.